Effect of Width of Blaze and Stimulant (In Resin Tapping) on the Growth of Chirpine (Pinus roxburghii Sargent) - Verma, V. P. S.; Pant, S. P. (Indian Forester, 1978)
The width of annual rings was measured on 90 chirpine trees tapped for 5 years to different extent of their girth. Such measurements were also carried out on 9 untapped trees to compare the effect of tapping. The data showed that tapping significantly reduced the ring width during tapping period, the reduction being correlated to the effective width of the blaze. Tapping for 5 years with the normal (10 cm wide) blaze reduced the ring width by 14.3%. The trees tapped with the stimulant (20% solution of a mixture of Sulphuric and Nitric acids) showed on an average 3.5 percent greater decrease in the ring width than those tapped without any stimulant.